2011
DOI: 10.1021/ma102968w
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization of Thin Polycrystalline Diacetylene Films and Quenching of the Precursor Excited State

Abstract: International audienceMicrocrystalline films of the diacetylenes 4BCMU and 3BCMU were prepared by vacuum evaporation and polymerized by UV irradiation. A method for determining the absolute polymer content X in films has been developed. In 4BCMU the reaction rate is strongly decreased beyond X similar to 0.3. Existing models fail to fit the kinetics. A numerical model based on quenching of the monomer excited state, the initiation precursor, by energy transfer to a nearby existing chain is developed and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 76 publications
1
18
0
1
Order By: Relevance
“…These authors have also reported that photopolymerization does not go to completion, or at least not beyond a polymer content of 50%. It has been reported that complete polymerization would in principle be possible but will not take place because photo‐degradation of the photoproducts will limit the overall conversion . In addition, the researchers found it necessary to use a solvent‐washing approach to remove residual monomer in the NRA analysis, adding additional labor and potential sources of error in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have also reported that photopolymerization does not go to completion, or at least not beyond a polymer content of 50%. It has been reported that complete polymerization would in principle be possible but will not take place because photo‐degradation of the photoproducts will limit the overall conversion . In addition, the researchers found it necessary to use a solvent‐washing approach to remove residual monomer in the NRA analysis, adding additional labor and potential sources of error in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that complete polymerization would in principle be possible but will not take place because photo-degradation of the photoproducts will limit the overall conversion. 31,32 In addition, the researchers found it necessary to use a solvent-washing approach to remove residual monomer in the NRA analysis, adding additional labor and potential sources of error in this analysis. The dual imaging method described here offers the advantage of simpler sample preparation, higher sensitivity, and a more easily accessible technique, compared with the NRA-based method.…”
Section: Discussionmentioning
confidence: 99%
“…The saturation behavior arises from the reaction kinematics of the photopolymerization of diacetylenes, 40 and the intensity saturates because the number of monomer crystal sites that are not yet polymerized is becoming more scarce with dose. Moreover, the slowing down of the reaction rate can also result from increased quenching of the precursor state by neighbor polymer chains as put forward by Spagnoli et al 41 It is likely that both mechanisms play a role in the dose-response of EBT3 films.…”
Section: C Different Polymer Phases In Ebt3 Filmsmentioning
confidence: 99%
“…2C), indicating that the maximum of polymer fraction is obtained after irradiating 20 min at 1.4 mW cm -2 . As explained thoroughly in 26 , it is incorrect to assume a complete polymerisation of the sample. Indeed, taking a value of 2×10 5 cm -1 for the absorption coefficient of the PDA gives an order of magnitude of 10% polymer percentage.…”
mentioning
confidence: 99%
“…This effect is ascribable to plastic deformation of the crystals that steps in beyond a certain polymer fraction, causing a slight increase of the exciton energy. 26 In Fig. 2B, the fluorescence spectra after each irradiation of the same sample are shown.…”
mentioning
confidence: 99%